(untitled) (Research, Society and Development, 2022)
This manuscript aims to present about the moodle platform and its main synchronous and asynchronous tools that contribute to a meaningful learning for users. This virtual environment is the most used in the globe, and in Ceará we can refer to the State University of Ceará (UECE), one of the best universities in the state, being useful for this platform, in addition to also enjoying the e-learning mode that is a trend in teaching the distance nowadays, and its intensification was due to copious use of computers and the web has become more accessible to humanity. This article extends to a literature review. By the way, it provides students with better ways of building knowledge, in addition to being active, autonomous and protagonist participants. Furthermore, with the application of the moodle platform and the e-learning mode, excellent teaching is promoted, facilitating the internalization of content and consolidation of learning.